New House Ceremony - Rina Trie Syahputri; Tiarnita Maria Sarjani Br. Siregar; Ribka Manurung; Sandra Hutapea; Yoga Karosekali (Interdisciplinary Journal of Advanced Research and Innovation, 2024)
This research aims to find out about the new house ceremony, specifically in the Batak toba custom, by exploring and documenting what is known as "Mambongoti Bagas" practiced by the Batak tribe, especially the Toba subgroup. Mamongoti Bagas is an important ceremony since the house is a sacred place for Batak people, especially when it is new. This ceremony takes place in the owner's new house, and the goods used can vary. The method used is to observe the Mambongoti Bagas tradition of the Batak Toba tribe. The results of the research show the celebration of the new house of the tobayang Batak tribe is also called "Mambongoti Bagas" The ceremony begins with respect in the form of local cuisine, "Namalum" (pork neck) to Tulang and Tondong, and they will give ulos to the owner of the house (Suhut), blessings (pasu-pasu) to Suhu, Boru, and Sanina give food namely manuk (dayok), batur manggoluh and rice to Suhut, then prayers and advice.